Hypebaeus cooteri sp. nov., the nemoral species of soft-winged flower beetles (Coleoptera, Malachiidae) in North Asia - Tshernyshev, Sergei E. (Diversity)
A new species of soft-winged flower beetle, Hypebaeus cooteri Tshernyshev, sp. nov., external appearance very close to H. flavipes (Fabricius, 1787) but differs in shape of the elytral appendages and dark colouration of apical margin of the elytra is described from the Russian Far East. Phenomenon of disjunctive distribution of the new species from the main areal of the genus is discussed on the basis of nemoral faunogenesis during the Late Pleistocene and the Middle Holocene in dependence of broad-leaf forest distribution. Oak trees are considered as typical habitat of the genus Hypebaeus Kiesenwetter, 1863 on the basis of field study by Jonathan Cooter in Moccas Park National Nature Reserve on old oak trees in UK. H. flavipes, the nominative species of the genus Hypebaeus, is redescribed from the specimens collected in Great Britain. Illustrations of external appearance and special male characters for both species are provided.